Czesława Znamierowskiego koncepcje grupy społecznej i społeczności - Ziembiński, Zygmunt (Wydział Prawa i Administracji UAM, 1987)
Sociological conceptions of Cz. Znamierowski are relatively little known part of his rich and many-sided scientific output. The article calls the reader's attention to that theoretician's of law conceptions in the field of the theory of social collections, especially to the conceptions treating the spatially relatively isolated collectivities as the recruitment basis for the process of shaping the social groups (i.e. the process, due to which the collectivity becomes the community), as well as to the conceptions concerning the typology of natural and thetic groups, employing the notions of the theory of norms formulated by that author.
Czesław Znamierowski's conceptions of a social group and community